Investigation of different factors affecting the quality of spect images: A simulation study - Mahsa Noori-Asl (Journal of Medical Physics, 2020)
Background: Monte Carlo (MC) simulation codes are used extensively for modeling the nuclear medicine imaging systems, such as single photon emission computed tomography (SPECT) and positron emission tomography (PET). By using these codes, it is possible to set different imaging parameters and do various studies in the field of nuclear medicine imaging. Aims and Objectives: The aim of this study is to investigate the effective factors in improvement of the SPECT image quality by using MC simulation. Materials and Methods: In this study, we used the SIMIND MC simulation code and Jaszczak phantom containing six spheres with different diameters placed into a water-filled cylindrical phantom for consideration of the effects of different factors on quality of the images obtained from Tc-99m SPECT imaging system. The assessment criteria used to investigate these factors included image contrast, signal-to-noise ratio (SNR) and relative noise of the background (RNB). Results: The results of this study show that the right choice of the arc of rotation, the image matrix size, the number of angular views, type of the collimators, and also filters used in the image reconstruction affect the quality of SPECT images. Also, we show that use of scatter correction methods can improve the image quality. Conclusion: The MC simulation is a suitable tool for investigation of different factors affecting the quality of SPECT images, essentially in the studies based on the energy spectrum, such as the evaluation of the scatter correction methods.